PENGARUH TRANSISI AKUNTANSI DIGITAL TERHADAP LAPORAN KEUANGAN - Hamidah, Aqilah Putri; Nugroho, Ibnu Cahyo (Jurnal Pijar, 2024)
This research aims to calculate how much influence the digital accounting transition has on financial reports and how digital accounting technology influences financial reports. The research method used is a quantitative method. The data collection technique used in this research is through a quantitative descriptive approach obtained from questionnaire data given to respondents. Data were analyzed using IBM SPSS Statistics 22. Data analysis techniques were carried out using validity tests, reliability tests and hypothesis tests. This research shows that the results show that skills in using digital accounting, the quality of financial reports is declared valid and skills in using digital accounting have a positive effect on the quality of financial reports. This digital accounting transformation must be utilized optimally to improve the preparation of financial reports. However, we still pay attention to data security and social impacts. Companies and educational institutions are also expected to take proactive steps in facing this change, both through training and investing in technology and infrastructure that supports accounting digitalization.